A conceptual model on preparing student in mechanical engineering program at Malaysian vocational colleges - Yusri Kamin, Mohd. Fa'Iz Ahmad (International Journal of Pure and Applied Mathematics, 2018)
Technical and Vocational Education (TVE) has undergone several policy changes since its inception and this is apparent in Transformation of Vocational Education (TPV) which was introduced in 2013. Through this transformation, Vocational Schools (VS) were upgraded to vocational colleges (KV) and this effort shows Malaysian government’s efforts to boost (TVE) as an institution of excellence that is able to produce superior human capital and adapt the challenges of globalization and technological changes. This esearch was conducted to develop a Model of Preparing Mechanical Program at College Vocational in Malaysia. Specif- ically, this research identified the possessed levels of competences of college vocational students in terms of technical and employability skills, examined the teaching methods employed in the teaching of mechanical in the college vocational, identified the challenges faced by mechanical program teachers with respect to instructional delivery, determined the adequacy of infrastructural facilities for effective teaching and learning of mechanical program in the college vocational and determined the adequacy of workshop tools and equipment in mechanical program for effective skills acquisition in mechanical program. These changes are closely related to factors such as technical skills, teaching methodology, infrastructure, and materials and equipment. This study used Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structures) to analyze the relationship between variables and tested the model to be developed. Five hundred and sixty-six students (566) of mechanical engineering program and seventy-five (75) mechanical engineering lecturers from vocational colleges in the southern states of Malaysia responded to the questionnaire conducted. It is recommended that the institutions continue to monitor and report on the needs required by industry. The higher authorities should also provide all the necessary facilities in line with the current technology and all parties involved should ensure that all the facilities are well maintained. In addition, continuous maintenance should be done to ensure that the facilities are at an optimum level and safe to be utilized.